2011
DOI: 10.1152/physiolgenomics.00121.2011
|View full text |Cite
|
Sign up to set email alerts
|

Homogenous protein programming in the mammalian left and right ventricle free walls

Abstract: Despite identical cardiac outputs, the right (RV) and left ventricle (LV) have very different embryological origins and resting workload. These differences suggest that the ventricles have different protein programming with regard to energy metabolism and contractile elements. The objective of this study was to determine the relative RV and LV protein expression levels, with an emphasis on energy metabolism. The RV and LV protein contents of the rabbit and porcine heart were determined with quantitative gel el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 33 publications
5
30
0
Order By: Relevance
“…Application of this technology revealed that the left and right ventricle of the mouse has negligible differences in their coreproteome. While this manuscript was in press, a comparative proteome study of the left and right ventricle of the rabbit heart revealed similar results (31).…”
Section: Discussionsupporting
confidence: 53%
“…Application of this technology revealed that the left and right ventricle of the mouse has negligible differences in their coreproteome. While this manuscript was in press, a comparative proteome study of the left and right ventricle of the rabbit heart revealed similar results (31).…”
Section: Discussionsupporting
confidence: 53%
“…The data of Hyder et al (5) suggest that brain P s and ΣP ns are also fixed across wide ranges of neuronal activity within a species brain and, if properly normalized, also apply across a wide range of brain sizes and cognitive abilities. A linear relationship between neuronal activity and energy metabolism using 13 C NMR estimates of neurotransmitter cycling and oxidative ATP production (7,8) has also been observed, consistent with fixed values of brain P s and ΣP ns . Taken together, these results suggest that the efficiency of the cellular mechanisms empowering brain-signaling activity by aerobic metabolism are very similar over a wide range of activity and between species.…”
supporting
confidence: 62%
“…Thus, in the liver the metabolic capacity per cell increases with decreasing animal size. In contrast, the cardiac [COX] and PVM remains constant with the heart size (10) and chamber (13), indicating that the metabolic capacity per cell of heart muscle remains essentially constant. What is the effect of brain size on neuronal PVM?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Phillips et al (29) have shown that overall protein expression levels in the normal, nondiseased rabbit LV and RV are similar. These authors suggested that the lower metabolic stress of the RV would approach that of the LV at maximal workloads and that the identical protein levels associated with energy conversion and function in the LV and RV would therefore be differentially stressed at maximal workloads.…”
Section: H704mentioning
confidence: 98%